Street Dance Training Might Increase the Neural Response to Pleasant Emotional Stimuli - Siwei Miao; Yingdong Yan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study aims to assess whether training in street dance can enhance neural responses to positive emotional stimuli. A total of 30 participants were recruited and divided into two groups: a training group comprising 10 men and 5 women, and a control group with an identical composition. The training group engaged in 60-minute street dance sessions three times per week for four weeks. The control group maintained their usual daily routines and was explicitly instructed to avoid any new physical exercise during the study. Emotional states were assessed in the training group before and after the training programme. Functional magnetic resonance imaging (fMRI) data were collected in two sessions: one prior to and one following the training period. A significant increase in enjoyment was observed after the first session (17.99±2.58 to 23.06±3.47, P = 0.02) and the twelfth session (17.02±2.06 to 24.11±3.14, P = 0.003). Additionally, anxiety levels decreased significantly immediately after exercise (13.21±2.22 to 8.99±1.57, P = 0.03), with further reductions following the twelfth session (13.04±1.89 to 8.01±1.63, P = 0.04). The CES-D scores in the training group increased from 11.99±1.63 to 14.03±2.04, whereas in the control group, they changed from 10.96±1.21 to 12.69±2.55. However, no statistically significant interaction between groups over time was identified (P = 0.14). Brain regions associated with processing positive emotional stimuli included the cuneus, precuneus, insula, temporal pole, pMCC, and angular gyrus. Additionally, the training group exhibited enhanced neural responses in the cuneus, somatosensory region, IPL, and SPL when processing negative emotional stimuli. This study examined how street dance training influenced neural responses to emotional stimuli in young, healthy individuals. Both positive and negative emotional cues elicited activity in the occipital and posterior parietal cortices.